1997
DOI: 10.3109/08037059709061932
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Viscosity, Blood Pressure and Cardiovascular Risk Factors in Healthy Blood Donors

Abstract: Whole blood viscosity contributes to the total peripheral resistance and has been suggested to be a risk factor for cardiovascular disease. Whole blood viscosity was measured using a direct technique in 105 healthy blood donors and in addition to establishing our reference values, the relationship to blood pressure and other cardiovascular risk factors was assessed. Whole blood viscosity correlated with systolic blood pressure (r = 0.29, p = 0.003), cholesterol (r = 0.21, p = 0.034), cholesterol/HDL cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 15 publications
3
29
0
2
Order By: Relevance
“…WBV was measured at shear rates of 0.5, 1.1, 5.8, and 201 s Ϫ1 in EDTA anticoagulated blood with a rheometer (CS 10, Bohlin Instruments Ltd) using a double-gap technique, which we have previously described and validated in detail. 3,20 …”
Section: Bp and Biochemical Measurementsmentioning
confidence: 99%
“…WBV was measured at shear rates of 0.5, 1.1, 5.8, and 201 s Ϫ1 in EDTA anticoagulated blood with a rheometer (CS 10, Bohlin Instruments Ltd) using a double-gap technique, which we have previously described and validated in detail. 3,20 …”
Section: Bp and Biochemical Measurementsmentioning
confidence: 99%
“…These dynamical and rheological features of blood flow determine the characteristics of the micro-vascular circulation that includes the flow in arterioles, venules, and capillaries. It has been reported that micro-vascular blood flow is crucial to maintaining metabolic balance in tissues, and the characteristics of blood flow can be used as indicators for the risk of circulatory diseases such as diabetics, hypertension and stroke [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased viscosity may be one mechanism by which cardiovascular risk factors promote atherosclerosis and plaque formation (Lee et al 1998). Whole-blood or plasma viscosity is inversely related to insulin sensitivity (Høieggen et al 1998) and strongly related to metabolic risk factors (Fossum et al 1997).Given this background, the question of whether increased water intake reduces blood viscosity is of interest, but only limited data exist. We examined the effect of increasing short-term water intake on whole-blood viscosity and its correlates in subjects with cardiovascular risk factors in a randomised, paralleldesign, controlled clinical trial that included a control group and a group that ingested 1 litre blueberry juice/d providing a comparison with an energy-containing fluid.…”
mentioning
confidence: 99%
“…Subsequently, whole-blood viscosity and packed cell volume were shown to be independent predictors of coronary events (Danesh et al 2000). The major CVD risk factors are independently associated with whole-blood or plasma viscosity (Bonithon-Kopp et al 1993;Fossum et al 1997). Thus, increased viscosity may be one mechanism by which cardiovascular risk factors promote atherosclerosis and plaque formation (Lee et al 1998).…”
mentioning
confidence: 99%